Physical activity, screening cancer, and savings rate as indicators of health responsibility - Rogalska, Anna (Journal of Education, Health and Sport, 2024)
Introduction: The health of individuals can change gradually over time as a result of the choices they make. Aim: The study aimed to examine indicators such as physical activity levels, screening participation, and household savings in the context of their role as potential measures of individual health responsibility. The second aim was to identify cognitive barriers and motivations influencing physical activity, breast and cervical cancer screening participation, and money-saving habits. Material and methods: The analysis used available data on physical activity, the screening level (for breast and cervical cancer), and household savings rates. Then, the data for Poland were presented against the background of available averages for the European Union. The data came from Eurostat, Eurobarometer - the official survey instrument used by the European Parliament. Results: According to Eurobarometer data, 65% of respondents in Poland have never been physically active in 2022 (vs in the European Union 45%). In 2022, the percentage of women who were screened for cervical cancer in Poland was 34% of women. And the cervical cancer program (cytology) was used by 10.9% of people. In 2022, the household saving rate was 12.7 % in the EU, and in Poland -2.89%, where the lowest rate occurred in Greece and the highest in Germany (Eurostat data). Conclusion: The low level of physical activity and participation in screening tests in Poland, compared to EU countries, highlights the need to intensify public health promotion activities. Additionally, promoting saving as an important element of health responsibility can not only improve the financial well-being of citizens but also have a positive impact on their mental health.